Changes in uterine electromyography according to cervical dilatation in the first stage of labor - Neža Sofija Pristov; Ela Rednak; Ksenija Geršak; Andreja Trojner Bregar; Miha Lučovnik (IMR Press, 2021)
Background: Myometrial contractile activity can be evaluated by recording uterine electromyography (EMG) non-invasively from the abdominal surface. Uterine EMG has been shown to detect contractions during labor as reliably as tocography (TOCO) and intrauterine pressure catheters. To evaluate whether changes in uterine EMG throughout the first stage of labor correlate with advancing cervical dilatation. Methods: Uterine EMG was recorded from the abdominal surface for 30 minutes in 32 women during the first stage of labor at term. Women were divided in three groups according to cervical dilatation at the time of EMG recording: <3 cm (n = 4), 3-5 cm (n = 19), and 6-10 cm (n = 9). Power density spectrum (PDS) peak frequencies within EMG bursts were compared between groups using ANOVA (p < 0.05 significant). Bonferroni post-hoc test was used for pair-wise comparison among groups. Results: PDS peak frequencies were significantly different in the three groups (p < 0.001). PDS peak frequency in the ≥6 cm dilatation group (0.52 ± 0.06 Hz) was significantly higher than in the <3 cm group (0.41 ± 0.02 Hz; p = 0.001) and 3 to 5 cm group (0.44 ± 0.04 Hz, p = 0.001). Difference between <3 cm and 3 to 5 cm groups was not statistically significant (p = 0.55). Discussion: Uterine EMG PDS peak frequencies increase with increasing cervical dilatation during the first stage of labor.